The Effects of Real-Time Feedback on Effort and Performance: Evidence from a Natural Quasi-Experiment - Margolin, Maximilian; Reimer, Marko; Schaupp, Daniel (Management Science, 2025)
New digital technologies allow companies to provide employees with performance feedback in real time. We investigate the causal effects of such real-time feedback on individual effort and the quality of initial (prefeedback) and final (postfeedback) decisions by exploiting a natural quasi-experiment in the setting of professional soccer refereeing. Our results suggest that real-time feedback has differential effects for experienced compared with inexperienced agents. Specifically, we find some evidence that experienced agents decrease their effort under real-time feedback without harming the quality of their initial decisions. This results in better final decisions because real-time feedback allows agents to correct wrong initial decisions upon feedback. In contrast, inexperienced agents increase their effort, but make worse initial decisions. Upon feedback, they manage to compensate for their increased number of wrong initial decisions, but see no improvement in the quality of final decisions. This paper was accepted by Ranjani Krishnan, accounting. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.02084 .